The robustness of the determinants of overall bank risks in the MENA region - Tarek Ibrahim Eldomiaty; Amr Youssef; Heba Mahrous (Journal of Risk and Financial Management, 2022)
Purpose: The banking sector in the MENA region is exposed to financial risks that originate from both the internal and external environment. Related studies in the literature have reached inconclusive determinants of the overall risks to banks. This paper examines the robustness of the determinants cited in the related literature. Design/methodology/approach: This paper examines the country-specific and bank-specific factors that affect banks' Z-score (being a proxy for the overall bank risks) in the MENA region. The sample banks consist of 33 listed commercial banks operating in six countries in the MENA region. Balanced panel data over 20 years (2000 to 2020) was examined, having a total of 660 observations. The Pooled Ordinary Least Square estimation (OLS) was used to carry out the empirical analysis. Findings: The findings of this paper showed that the robust determinants of overall bank risks are follows: (a) The unemployment rate had a negative effect on high overall bank risks in the period 2000-2010, (b) The financial crisis had a positive effect on the MENA overall bank risks in the period 2000-2010, but only for the low overall bank risks, (c) A robust and negative effect of cost/income ratio was observed in the period 2010-2020 only for high overall bank risk, (d) Low overall-risk banks were able to manage overall risks in a shorter time than high overall bank risks, and (e) In terms of the country-wide effect, the results for Egypt only showed that the overall bank risk had positive effects in the period 2000-2010, but negative and significant effects in the period 2011-2020 where overall bank risks reduced. Originality: This paper offers robust findings in the controversy around the determinants of overall bank risks in the MENA region, which is beneficial in light of the fact that the literature thus far has not reached a consensus regarding this issue.
Keywords: G21; 650; Z-score; bank-specific; country-specific; MENA region; robustness